A Modified Spectral Phase Conjugation Algorithm for Quadratic Programming: Application to Water Resources Planning Problems. (May 2019) - Kong, Xiangming; Hao, Zhenda; Yang, Aili
Abstract: Water resources management system has been a major concern since it gives necessities of human-living as well as promoting economic development. Therefore, how to establish valid and accurate water management schemes for water managers to satisfy the demands from water users, is of great significance. In this study, a modified spectral phase conjugation algorithm for quadratic programming (MCQP) is developed for water resources management systems. The model is detived by modifying the search direction within spectral phase conjugation algorithm. MCQP can efficiently solve nonlinearity in the objective function and linearity in the constraint which lead to complexes in water resources management systems. Results show that reasonable solutions have been obtained to support the rational development of water resources management. They can help water managers to identify desired policies under variou economic and environmental constraints. MCQP can be further applied to other resources management systems with mixed nonlinear and linear factors.